The Social Impact of The Existence of A Palm Oil Company: The Social Impact of The Existence of A Palm Oil Company - Yasin, Muhammad; Anwar, Kasyful; Hayat, Atma; Yuliani, Rahma (GOVERNORS, 2023)
This research aims to find out the impact and the level of community social welfare and to determine the relationship between the impact of oil palm land on the community welfare in Kapuas District, Kapuas Regency, Central Kalimantan Province. This research employed qualitative descriptive analysis. The data were analyzed using data triangulation techniques. The findings of this study indicated that, based on observations and interviews conducted with 30 respondents from the community of Anjir Kalampan Village, West Kapuas District, Kapuas Regency, Central Kalimantan, and with the support of other sources, it is known that the establishment of PT. Kapuas Sawit Sejahtera has had a socio-economic impact on the surrounding community. The Socio-Economic Condition is a condition that reflects the economic position of society in its social structure, with an impact that can be structured or unstructured. However, the impact is minor because there is no direct contribution or influence on the village's existing infrastructure/facilities, such as repairing roads, schools, and health centers. This is due to the company's ongoing conflicts and inability to operate normally, as a result of which the company has always suffered losses.